Exploring relationships between Lipid parameters and Serum Vitamin-D deficiency. - Farhan Haleem; Ghulam Basit; Riaz Hussain; Sabir Ali; Beenish Imam; Muhammad Ali Khan; Ashad Ahmed; Syed Jibran Ashraf (International Journal of Endorsing Health Science Research, 2023)
Background: Vitamin D deficiency is a prevalent global health concern. To investigate the relationship between serum vitamin D levels and lipid parameters. Methodology: A prospective observational cohort study was carried out at Sindh Government Hospital Liaquatabad from October 2021 to February 2022. The study included a total of 171 participants, comprising both males and females aged 18 years or older, with vitamin D levels falling below 30 ng/ml. Participant selection employed a consecutive non-probability sampling method. Serum vitamin D levels were quantified using the COBAS method. Dyslipidemia and hypertriglyceridemia were defined based on established clinical guidelines. Exclusion criteria encompassed individuals with specific medical conditions and those currently using medications. Statistical analysis was conducted using SPSS version 22.0. Results: Out of the 171 participants, the majority were female, constituting 129 (75.43%), while 42 (24.56%) were male. Interestingly, a higher prevalence of vitamin D deficiency was observed among younger patients, with the age group of 30-39 years displaying the highest rate of vitamin D deficiency. Regarding lipid profiles, dyslipidemia was significantly more common in female patients (50.87%) compared to their male counterparts (5.26%). However, it's noteworthy that male patients exhibited higher triglyceride levels (167.21 ± 89.64 mg/dl) than females. Conclusion: This study reveals a strong relationship between vitamin D deficiency and lipid parameters.